ANALISIS STRATEGI PENINGKATAN PENJUALAN PADA PT HASJRAT ABADI OUTLET YAMAHA SEMPAN - Halisya Halisya; Anggela Jessica Bolung; Tri Apriyono (Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the sales increase strategy at PT. Hasjrat Abadi Outlet Yamaha Sempan. The research method used in this study is a descriptive method. In this study, the data collection technique used is a questionnaire. To determine the sales increase strategy, the researcher used SWOT analysis. The results of this study indicate that the sales increase strategy at PT. Hasjrat Abadi Outlet Yamaha Sempan is located in quadrant 4 of the WT strategy, which has alternative strategies such as: knowing what consumers want by understanding the market in depth, providing a comfortable place, promoting creative products by utilizing existing technology and selling trending products